Analysis of the Effectiveness of Using Google Classroom and Science Learning During the COVID-19 Pandemic - Shalsa Billa Ardhana Neswary (Indonesia Emerging Literacy Education, 2022)
The rapidly widespread spread of COVID-19 in Indonesia has made the Indonesian government make policies, one of its policies is to carry out distance learning activities. This study aims to analyze the effectiveness of using Google Classroom in science learning during the COVID-19 pandemic. This research uses a literature study by reviewing 30 articles or journals published in the 2018-2022 period and comes from Google Scholar and several international journals that come from trusted and accountable websites. The data obtained will then be analyzed using qualitative analysis. The results showed that: (1) The use of Google Classroom is effectively used in science learning during the COVID-19 pandemic, (2) The advantages of using Google Classroom in science learning during the COVID-19 pandemic are that it can improve analytical skills, improve science literacy skills, and grow students' character in science learning, (3) The weakness of using Google Classroom in science learning during the COVID-19 pandemic is that students have difficulty in receiving material, especially those that require calculations such as mathematics, chemistry, and physics